2020
DOI: 10.3390/su12041503
|View full text |Cite
|
Sign up to set email alerts
|

Applying Social Network Analysis to Identify Project Critical Success Factors

Abstract: A key challenge in project management is to understand to which extent the dynamic interactions between the different project people-through formal and informal networks of collaboration that temporarily emerge across a project´s lifecycle-throughout all the phases of a project lifecycle, influence a project's outcome. This challenge has been a growing concern to organizations that deliver projects, due their huge impact in economic, environmental, and social sustainability. In this work, a heuristic two-part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
140
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(143 citation statements)
references
References 53 publications
3
140
0
Order By: Relevance
“…The literature also shows that the adoption of an ambidextrous leadership style (characterized by the exploitation of present conditions to optimize current business model operations, while simultaneously exploring new opportunities that contribute to redefining business models by taking decisions in a pioneering, risky way) increases the chances of achieving sustainable competitive advantages [4,5]. In addition, the literature shows that the ability to work in cooperative networks in both organizational and individual levels is a critical factor for an organization to achieve success and generate actionable and unique knowledge [2,[6][7][8]. In fact, the latest research in organizational theory and management argues that although individual knowledge and skills are important, the ability to work in cooperative networks is almost always twice as critical to achieve success [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature also shows that the adoption of an ambidextrous leadership style (characterized by the exploitation of present conditions to optimize current business model operations, while simultaneously exploring new opportunities that contribute to redefining business models by taking decisions in a pioneering, risky way) increases the chances of achieving sustainable competitive advantages [4,5]. In addition, the literature shows that the ability to work in cooperative networks in both organizational and individual levels is a critical factor for an organization to achieve success and generate actionable and unique knowledge [2,[6][7][8]. In fact, the latest research in organizational theory and management argues that although individual knowledge and skills are important, the ability to work in cooperative networks is almost always twice as critical to achieve success [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the literature shows that the ability to work in cooperative networks in both organizational and individual levels is a critical factor for an organization to achieve success and generate actionable and unique knowledge [2,[6][7][8]. In fact, the latest research in organizational theory and management argues that although individual knowledge and skills are important, the ability to work in cooperative networks is almost always twice as critical to achieve success [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, on the one hand, SNA was implemented to understand how to build the most efficient working teams [ 20 ]. On the other hand, Nunes and Ambreu [ 21 ] used SNA to determine critical success factors in working projects and found that teamwork efficiency plays a fundamental role.…”
Section: The Role Of Non-technical Skillsmentioning
confidence: 99%
“…At last, the authors reviewed the database of this journal, mainly finding aspects of Social Networks, where the importance of understanding the relation between project dynamic interactions of the different project stakeholders and its performance has been mentioned [37]. Still, it has not been addressed through LAP.…”
Section: State Of the Art And Practicementioning
confidence: 99%